Pemberian Makanan Pendamping ASI (MPASI) Sesuai Dengan Usia Bayi Di Desa Bawang Kecamatan Pesantren Kota Kediri - elin soyanita; Dian Kumalasari (Fakultas Ilmu Kesehatan, 2019)
ABSTRACT The growth period of infants and toddlers is the most valuable period. In every step and development parents have the desire to give their best. One of the most important times is when the baby starts eating complementary foods. If the complementary food provided is not suitable, it can cause the baby to be malnourished and can become malnourished if not treated properly. The purpose of this study was to determine the factors associated with complementary feeding according to the age of the baby. This study is an analytical study using a cross sectional approach, the subjects studied were mothers who have children over 6 months of age who came to the posyandu onion village, pesantren district, Kediri district as many as 34 people. Statistical analysis with Chi square test (Chi Square). The results of the study showed that respondents gave complementary foods for ASI at yaitu 6 months, which were 64.7%, respondents received information about complementary foods as much as 76.5%, respondents who had good knowledge were 70.6% and had a positive attitude about giving complementary foods as much as 67.6%. The results of statistical analysis showed that there was no relationship between the source of information with complementary feeding according to age, there was a relationship between knowledge and attitude with supplementary feeding according to age. Health workers can further improve health education or counseling about complementary feeding. Keyword : Knlowledges, Attitude, sources of information, MP-ASI